Construction of a Knowledge Test on Papaya Ring Spot Virus Management Practices - Satpathy, Bineeta; Sahoo, Nirjharini (Indian Journal of Extension Education, 2025)
The study was conducted during 2024–25 to develop and standardise a scientifically sound knowledge test for assessing papaya farmers’ knowledge of Papaya Ring Spot Virus (PRSV) management practices in Bihar. An initial pool of 35 dichotomous items was prepared through an extensive literature review, expert consultation, and extension manuals. These items were pre-tested with 30 non-sample farmers, and item analysis was performed using the Difficulty Index, Discrimination Index, and Point-Biserial Correlation. Based on psychometric evaluation, 25 items representing preventive, cultural, chemical, and biological management practices were retained. The finalised test demonstrated high reliability, as indicated by KR-20 (0.92), split-half reliability (0.928), and Cronbach’s alpha (0.968), while content validity was confirmed through expert judgment. The standardised tool provides an objective and reliable method to assess knowledge gaps, facilitate targeted training programmes, and evaluate extension interventions. It holds potential for broader application in papaya-growing regions to strengthen PRSV management and promote sustainable papaya cultivation.